Alef and Shem: Original artwork. Issue 1 (2nd January 2019) - Gershoni, Sharon
Abstract: Artist and scientist Sharon Gershoni presents here two works of her art in different mediums. Alef is a series of drawings made with Japanese sumi ink on washi paper and is a reflection on the first letter of the Hebrew alphabet, alef . Shem (Name) is a photograph exposing the symbols and attributes of women in Western art and thought.